Development of Renewable Photobioreactor (FBR) Technology with Fluid Hydrodynamics System-Online Monitoring Microcontroller as SNI Standardized Pure Oxygen Producer - Hadiningrat, Mahendra Satria; Sari, Mayang; Sunardi, Ninik Nigusti Ayu (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2022)
This photobioreactor research was carried out using Chlorella vulgaris algae as an O2-producing reactor and optimizing light energy as its energy source, with dimensions of 40x50x60 cm with control of pH, temperature, and chemical visibility factors. Variations are given by providing a supply of CO2 in both types of photobioreactors. Then it can be seen the concentration of O2 produced from the photobioreactor and its ability to overcome CO2 gas emissions. The use of glass as a reactor-making material is because glass is able to absorb visible light wavelengths in the range of 400–750 nm where at that wavelength microalgae can live and reproduce well. Before selecting the lamp used for the photobioreactor system. Measurements were carried out on two photobioreactors, namely, photobioreactors supplied and not supplied with CO2, and using three types of light sources, namely halogen lamps, LEDs, and sunlight. The maximum oxygen concentration value was produced by the photobioreactor supplied with CO2. The average percent error of the designed tool is 1.383% which is obtained by comparing the value of the designed tool with the reference measuring instrument.